2008
DOI: 10.1097/qad.0b013e3282f29478
|View full text |Cite
|
Sign up to set email alerts
|

Frequent polymorphism at drug resistance sites in HIV-1 protease and reverse transcriptase

Abstract: Background-Failure of antiretroviral therapy may result from the selection of pre-existing, drug-resistant HIV-1 variants, but the frequency and type of such variants have not been defined. Objective-We used single genome sequencing (SGS) to characterize the frequency of polymorphism at drug resistance sites in protease (PR) and reverse transcriptase (RT) in plasma samples from antiretroviral naive individuals. Methods-A total of 2229 pro-pol sequences in 79 plasma samples from 30 patients were analyzed by SGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 11 publications
4
82
0
Order By: Relevance
“…It is, therefore, important to understand the frequency of such mutations, as well as their variability and kinetics of appearance in drug-naïve infected individuals. Although we (14,19, We have used UsASP to investigate the evolution of drug resistance before and after EFV monotherapy in 2 RT-SHIV mne infected macaques. We were able to reproducibly detect the K65R and M184I drug resistance mutations before and after drug exposure and observe how they were maintained in the same proportion relative to the total virus population, consistent with the predicted balance between mutation and selection at these sites.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, important to understand the frequency of such mutations, as well as their variability and kinetics of appearance in drug-naïve infected individuals. Although we (14,19, We have used UsASP to investigate the evolution of drug resistance before and after EFV monotherapy in 2 RT-SHIV mne infected macaques. We were able to reproducibly detect the K65R and M184I drug resistance mutations before and after drug exposure and observe how they were maintained in the same proportion relative to the total virus population, consistent with the predicted balance between mutation and selection at these sites.…”
Section: Discussionmentioning
confidence: 99%
“…According to Poisson's distribution, ϳ80% of wells with detectable HIV-1 RNA were expected to contain a single expressing HIV-1 provirus. Single-genome sequencing (SGS) (11,12) revealed that three of four wells had monotypic sequences with infrequent single-base-pair differences within the known error rate of SGS (ϳ1.1 ϫ 10 Ϫ4 errors/nucleotide) ( Fig. 3) (11), confirming that most wells with detectable HIV-1 RNA contained a single expressing provirus.…”
Section: Iv-1 Virion Production From Resting Cd4mentioning
confidence: 94%
“…To compare the intracellular populations identified using the single-proviral sequencing assay to HIV-1 RNA populations found in plasma collected before initiation of antiretroviral therapy, we performed singlegenome sequencing (SGS) on the plasma samples from each of the eight patients as described earlier (48)(49)(50). To extract viral RNA from plasma collected during suppressive therapy, we used a modified version of the SGS method.…”
Section: Methodsmentioning
confidence: 99%